Parallel computational fluid dynamics : parallel computings and its applications : proceedings of the Parallel CFD 2006 Conference, Busan city, Korea (May 15-18, 2006) - Kwon, J. H. (Jang Hyuk), 1949- (Elsevier, 2007)
The proceedings from Parallel CFD 2006 covers all aspects of parallel computings and its applications. Although CFD is one of basic tools for design procedures to produce machineries, such as automobiles, ships, aircrafts, etc., large scale parallel computing has been realized very recently, especially for the manufactures. Various applications in many areas could be experienced including acoustics, weather prediction and ocean modeling, flow control, turbine flow, fluid-structure interaction, optimization, heat transfer, hydrodynamics. - Report on current research in the field in an area which is rapidly changing - Subject is important to all interested in solving large fluid dynamics problems - Interdisciplinary activity. Contributions include scientists with a variety of backgrounds.